Mining and the Analysis of the Effects of the Disaster in Maceió : Uma Análise Sociourbanística dos Efeitos do Desastre em Maceió - Lima Filho, Walter Araújo de; Levino, Natallya de Almeida (Technical and Scientific Journal Green Cities, 2024)
The study aims to identify, from a socio-urbanistic perspective, the impacts caused by the mining disaster in Maceió and the measures taken by the stakeholders involved in the damage repair. The significance of the study is aligned with the need to understand the effects of this disaster, which is considered one of the largest ongoing in a metropolitan region in Brazil and Latin America. The results indicate that the impacts are substantial, altering the structural dynamics of the territory in both material and immaterial aspects. Moreover, based on the perception of the mitigation measures and the theoretical context raised, it is necessary to apply measures and reparations from the individual's perspective to effectively resolve the negative effects, as the observed impacts go beyond the material and compensatory realm. As a contribution, the study provides additional theoretical support to conclude the disaster's impacts in the socio-urbanistic context and offers social implications by qualifying the measures already presented by the stakeholders involved in the process. It also emphasizes the need for specialist collaboration in understanding the scope of the impacts and the necessity to place the individual at the center of resolutions addressing the disaster's implications on the local context.
Keywords: Disaster; Socio-environmental impacts; Socio-urbanism